Myocardial Bridging as a Trigger in Angina With No Obstructive Coronary Artery Disease - Beijk, Marcel A.M.; Woudstra, Janneke; Vink, A. Suzanne; Bijsterveld, Nick R.; de Lind van Wijngaarden, Robert A.F.; Klautz, Robert J.M. (JACC. Case reports, 2024)
We present 2 patients with angina with no obstructive coronary artery disease and concomitant myocardial bridging. Despite maximal tolerated pharmacotherapy, symptoms remained. Invasive anatomical and hemodynamic assessment identified myocardial bridging as a contributing cause of angina. Following heart team discussion, both patients underwent successful coronary artery unroofing of the left anterior descending artery. [Display omitted]